Clinical Validation of the Defining Characteristics of the Nursing Diagnosis ‘Activity Intolerance’ in Patients With Acute Coronary Syndrome - Diana Isabel Cáceres Rivera; Luz Mileyde Jaimes Rojas; Luisa Yaneth Cristancho Zambrano; Jennifer Vanesa Acosta Barón; Diana Ivonne Cañon Gómez; Lyda Z. Rojas (Nursing Open)
ABSTRACT Aim To validate the defining characteristics (CDs) of the nursing diagnosis ‘Activity intolerance [00092]’ in patients with acute coronary syndrome (ACS). Design Cross‐sectional study. Patients over 18 years of age with a confirmed medical diagnosis of hospitalised ACS were included and those who were haemodynamically unstable, with alterations in the mental sphere or with communication limitations were excluded. The CDs were previously operationalised for standardised measurement and independently assessed by nurses. Results A total of 111 patients with ACS were studied. The CDs with prevalence > 50% were: generalised weakness (80.56 vs. 78.70%), discomfort on exertion (72.07% vs. 75.68%) and ECG changes (71.17% vs. 68.47%). Inter‐rater agreement for determining the CDs ranged from 0.69 to 1.00. Conclusions This study established the clinical validation of the CDs of the nursing diagnosis ‘Activity Intolerance [00092]’ in patients with ACS identifying three major CDs: EKG changes, generalised weakness and exertional discomfort. Patient or Public Contribution No patient or public contribution the research was developed in its entirety by the authors. Implications for the Profession and/or Patient Care The clinical validation of the defining characteristics of the activity intolerance diagnosis was conducted. This validation was based on operationalising each characteristic using commonly employed nursing scales and instruments. This process contributes significantly to the establishment of evidence‐based nursing practices. The customisation of nursing diagnoses gains further ground through the validation studies of NANDA‐I diagnoses. This process solidifies standardised nursing language as a valuable strategy in nursing care, providing substantial support for practical decision‐making. Among the evaluators, EKG changes, generalised weakness and discomfort on exertion emerged as the most frequently encountered defining characteristics with substantial agreement. This discovery offers crucial insights for devising individualised and collective care plans within coronary units.